2022
DOI: 10.3390/ijerph19116811
|View full text |Cite
|
Sign up to set email alerts
|

Return to Work of Healthcare Workers after SARS-CoV-2 Infection: Determinants of Physical and Mental Health

Abstract: Introduction. The SARS-CoV-2 pandemic has involved healthcare workers (HCWs) both as caregivers and as patients. This study is a retrospective cross-sectional analysis of the HCWs working in a third-level hospital in Central Italy who were infected with COVID-19 from March 2020 to April 2021. This research aims at identifying the physical and mental health outcomes of HCWs infected with COVID-19 who returned to work after the infection, the determinants of those outcomes, such as age and sex, and the identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 45 publications
3
13
0
Order By: Relevance
“…It is widely known that COVID-19 infection can result in several different ailments, denoted as post-COVID-19 symptoms or post-COVID-19 syndrome [8,36], which may last from several weeks to years [15]. These conditions challenge healthcare professionals' return to work [37] and can transform an infection that usually lasts 1 to 3 weeks into a long, complex illness. Post-COVID-19 symptoms can affect patients with all levels of disease severity as well as young, healthy people [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…It is widely known that COVID-19 infection can result in several different ailments, denoted as post-COVID-19 symptoms or post-COVID-19 syndrome [8,36], which may last from several weeks to years [15]. These conditions challenge healthcare professionals' return to work [37] and can transform an infection that usually lasts 1 to 3 weeks into a long, complex illness. Post-COVID-19 symptoms can affect patients with all levels of disease severity as well as young, healthy people [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…The individual and societal impact of this condition has not been fully understood yet. Various studies have shown how this syndrome leads to significant limitations in functional abilities and to a general reduction in quality of life; this is the case, especially, though not exclusively, in patients who have experienced a severe disease or have undergone a hospital stay [ 10 , 11 , 12 , 13 , 14 , 15 ]. A longitudinal cohort study recently performed in China showed that the population surviving COVID-19 after a hospital stay, even after two years from the acute illness, had more lasting symptoms and more residual pain or discomfort, as well as anxiety or depression, compared to controls [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the COVID-19 outbreak, the quality of sleep of nursing staff was significantly lower than that of other healthcare workers (Zare et al, 2022). When healthcare workers returned to work 3 months after SARS-CoV-2 infection, one-third of them reported worsening sleep patterns (Grazzini et al, 2022). It is not just common risk factors such as female sex, advanced age, persistent fatigue, and circadian rhythm changes that can cause insomnia.…”
Section: Discussionmentioning
confidence: 99%